2020
DOI: 10.1021/acs.jmedchem.9b01809
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent Benzimidazole Derivatives as Indoleamine 2,3-Dioxygenase-1 (IDO1) Inhibitors: From Structure-Based Virtual Screening to in Vivo Pharmacodynamic Activity

Abstract: In this study, a successful medicinal chemistry campaign that exploited virtual, biophysical, and biological investigations led to the identification of a novel class of IDO1 inhibitors based on a benzimidazole substructure. This family of compounds is endowed with an extensive bonding network in the protein active site, including the interaction with pocket C, a region not commonly exploited by previously reported IDO1 inhibitors. The tight packing of selected compounds within the enzyme contributes to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 74 publications
0
42
0
Order By: Relevance
“…These enzymes are first and rate-limiting enzymes of the kynurenine pathway, and implicated in neurodegenerative diseases and tumoral immune resistance; in particular, IDO1 and TDO have been demonstrated as important targets for cancer immunotherapy 23 , 24 , 25 , 26 . Although a number of IDO1 and TDO inhibitors have been reported and several inhibitors are in preclinical development 26 , 27 , 28 , 29 , discovery of new inhibitor chemotypes is still desirable at present. By comprehensive analysis of all reported complex structures for IDO1/TDO and the catalytic mechanisms of the tryptophan substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes are first and rate-limiting enzymes of the kynurenine pathway, and implicated in neurodegenerative diseases and tumoral immune resistance; in particular, IDO1 and TDO have been demonstrated as important targets for cancer immunotherapy 23 , 24 , 25 , 26 . Although a number of IDO1 and TDO inhibitors have been reported and several inhibitors are in preclinical development 26 , 27 , 28 , 29 , discovery of new inhibitor chemotypes is still desirable at present. By comprehensive analysis of all reported complex structures for IDO1/TDO and the catalytic mechanisms of the tryptophan substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Under these circumstances, a tritherapy comprising an inhibitor of IDO1, a checkpoint inhibitor, and an inhibitor of IL-4I1 could be an interesting avenue. Research for new IDO1 inhibitors continues actively [25,33]. Beyond cancer, targeting of IDO1 could also concern patients with metabolic disorders since obesity is associated with an increase of IDO1 activity in the gut, which hijacks L-Trp to the KP at the production expense of indoles by the microbiota.…”
Section: Enzymatic Modulation Dioxygenases Inhibitorsmentioning
confidence: 99%
“…As a follow-up to these studies, Serafini et al identified benzimidazoles as IDO1 inhibitors with the aid of a virtual screen of the IDO1 active site using the ZINC15 database [ 154 ]. Fifty of the top 500 molecules identified in this screen were purchased and evaluated in a cell-based assay measuring kynurenine levels in the A375 melanoma cancer cell line (which expresses high kynurenine levels when stimulated with INF-γ).…”
Section: Imidazoles As Inhibitors Of Other Targetsmentioning
confidence: 99%